2016
DOI: 10.1007/s12199-016-0514-6
|View full text |Cite|
|
Sign up to set email alerts
|

The relationship between hypertension and health-related quality of life: adjusted by chronic pain, chronic diseases, and life habits in the general middle-aged population in Japan

Abstract: These results may be due to the sex difference in the light of the perception for health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 54 publications
3
22
0
Order By: Relevance
“…We found that having a chronic disease was associated with poor HRQoL, based on both the EQ-5D index and the EQ-VAS score. Several studies have indicated that chronic diseases such as hypertension [ 25 ], diabetes [ 26 ], coronary heart disease [ 15 ], tuberculosis [ 16 ], multiple sclerosis [ 27 ], cancers [ 28 ], and allergic diseases [ 29 ] reduce HRQoL among adults. A study by Karyani et al [ 17 ] showed that chronic disease was an important determinant of HRQoL in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…We found that having a chronic disease was associated with poor HRQoL, based on both the EQ-5D index and the EQ-VAS score. Several studies have indicated that chronic diseases such as hypertension [ 25 ], diabetes [ 26 ], coronary heart disease [ 15 ], tuberculosis [ 16 ], multiple sclerosis [ 27 ], cancers [ 28 ], and allergic diseases [ 29 ] reduce HRQoL among adults. A study by Karyani et al [ 17 ] showed that chronic disease was an important determinant of HRQoL in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…The study of quality of life is an important part in chronic disease [ 18 ]; many researchers paid attention to hypertension patients [ 19 21 ]. But most of the questionnaires in their studies were SF-36, which could not reflect the most common and most direct questions affecting the quality of life in patients with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…We used a self-administered questionnaire handed to subjects by interviewers who were trained using standardized procedures; they explained the study and how to complete the questionnaire. A few days later, the completed forms, which were placed in sealed envelopes [11], were collected.…”
Section: Assessment Instruments and Definitionsmentioning
confidence: 99%
“…We conducted a cohort study named the Shika study in Shika Town of Ishikawa prefecture in Japan from 2011 [10,11]. Shika Town is located in Ishikawa prefecture, which is a rural area of Japan, and it has approximately 22,000 residents.…”
Section: Introductionmentioning
confidence: 99%